AKIBAT HUKUM DIKABULKANNYA PERUBAHAN ISI SURAT GUGATAN DALAM PERKARA HUKUM PERDATA DI WILAYAH HUKUM PENGADILAN NEGERI SANGATA - Ardi Lestari Tarihoran (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
Abstrack In the field of the law of civil aimed at regulating relations between law between individuals, so if there are disputes over rights that can not be resolved through these meetings and the consensus, the only way to go to get the settlement is legally delegate it to judicial authorities always authorized body to provide conflict resolution in question.      Whereas in the resolution of civil cases that occurred in the midst of people's lives by through judicial, juridical been no delineation of the procedure, in which first of all have to prepare the lawsuit which is being promoted by those who feel that their rights are violated by the other party.      In a lawsuit brought forward the letter to be published regarding the case and continued with what was required in order to be decided by a judge. But man as a creature of god usually would not infallible and mistakes, so there are times when the contents of this lawsuit is maintained, what is expected by the claimant will not hit its target.      The method used in analyzing the problems the author will use descriptive research method by way of Library Research and Field Research using data collection techniques through interviews and documentation, and after the data collected will be tested through deductive and inductive testing techniques.       From the data generated in the study that the issue of tort changes when viewed from the position of the defendant judges can not take full account of how the rights of the defendant if there is a change during the examination session in particular lawsuit has already begun.       And found that the lawsuit is amended by no means a guarantee for the benefit claimant only the legal effects defendant feel their rights are less protected.